Quantitative spatial resolution enhancement of reflection matrix optical coherence tomography for deep-tissue imaging - Cao, Jing; Fu, Ling; Wang, Pinghe; Liu, Qian (Journal of applied physics, 2023)
Multiple scattering poses a fundamental limitation in deep imaging, especially for high-resolution optical imaging methods. The amalgamation of reflection matrix measurements and optical coherence tomography (OCT) has afforded significant advantages for deep imaging through highly scattering media. To empirically exhibit the superior performance of reflection matrix OCT (RMOCT), this study proposes a unique method to ascertain the actual resolutions at each imaging point. In contrast to conventional theoretical lateral resolutions, these resolutions are derived by applying time-reversal decomposition to the time-gated reflection matrix. Moreover, the concept of contribution rate, which quantifies the imaging contributions for each point, is introduced by considering the local imaging point itself and its neighboring points. The contribution rate provides a quantitative evaluation of the imaging quality afforded by a system. To the best of our knowledge, this study represents the comprehensive assessment of the practical performance of RMOCT in terms of actual resolving power and imaging quality.